Implementation of the Role of Islamic Education Teachers in Building Student Character and Improving Student Achievement - Alya Hafizhah Lubis; Dzakiyyah Nur Syafrina; M. Fauzan Hamizan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The role of Islamic Religious Education (PAI) teachers is essential in shaping students’ character and improving their academic achievement. This study aims to analyze the implementation of PAI teachers' roles in building character and enhancing student achievement. The research method used is qualitative with a library research approach. The results indicate that PAI teachers act as educators, role models, facilitators, and motivators. Through character education integrated into learning, students develop discipline, responsibility, and moral values, which contribute positively to academic achievement.